Selecting Indicators for the Quality of Health Promotion, Prevention and Primary Care at the Health Systems Level in OECD Countries - Marshall, Martin (OECD Publishing, 2004)
This report presents the consensus recommendations of an international expert panel on indicators for health promotion and primary care. Using a structured review process, the panel selected a set of 27 indicators to cover the three key areas health promotion, preventive care and diagnosis and treatment in primary care. The report describes the review process and provides a detailed discussion of the scientific soundness and policy importance of the 27 indicators as follows ...
Keywords: Social Issues/Migration/Health